ANALISIS PENGARUH KUALITAS PRODUK, DESAIN PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIC HONDA VARIO MELALUI WORD OF MOUTH SEBAGAI VARIABEL INTERVENING DI DAERAH ISTIMEWA YOGYAKARTA - Muh. Fadhil Adli Yanuar; Uswatun Chasanah (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine the effect of product quality, product design and brand image on purchasing decisions of Honda Vario Automatic Motorcycles through word of mouth as an intervening variable in the Special Region of Yogyakarta. The method used in this study is quantitative with Partial Least Square (PLS) analysis. Data were collected through questionnaires distributed to respondents who are consumers of Honda Vario Automatic Motorcycles in the Special Region of Yogyakarta. The sampling technique used was Purposive Sampling, with a total of 100 respondents. Data processing using SmartPLS 4 with the conclusion that product quality and product design do not have a positive effect on purchasing decisions or word of mouth. Conversely, word of mouth has a positive effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions and word of mouth. In addition, word of mouth is only able to mediate the influence of brand image on purchasing decisions, but cannot mediate the influence of product quality and product design on purchasing decisions.